Analisis Hubungan Durasi Hemodialisis dengan Tekanan Darah pada Pasien Gagal Ginjal Kronik - Ferrina Putri Awwaliyah Zafikah; Suyanto Suyanto; Mohammad Arifin Noor (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Chronic kidney disease patients undergoing hemodialysis experience hemodynamic changes due to the ultrafiltration process and fluid shifts. The duration of hemodialysis may influence blood pressure, increasing the risk of either intradialytic hypertension or hypotension. This clinical variability highlights the need to analyze the relationship between hemodialysis duration and patient blood pressure. This study employed a quantitative design with a time series approach. A total of 106 hemodialysis patients at RSI Sultan Agung Semarang in July 2025 were selected based on inclusion criteria. Hemodialysis duration data were obtained from medical records, while blood pressure was recorded hourly on hemodialysis monitoring sheets. The relationship was analyzed using Pearson correlation, followed by a General Linear Model (GLM) to control for confounding variables. Results showed that patient blood pressure during hemodialysis varied according to measurement time. Repeated Measures GLM analysis indicated a significant difference in diastolic blood pressure across measurement times during hemodialysis (p < 0.05). Conversely, systolic blood pressure did not show a significant difference across measurement times (p > 0.05). The findings reveal that diastolic blood pressure changes significantly during hemodialysis in chronic kidney disease patients, whereas systolic blood pressure remains relatively stable.